The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/a14070213
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Deep Learning and Belief Rule-Based Expert System for Visual Sentiment Analysis under Uncertainty

Abstract: Visual sentiment analysis has become more popular than textual ones in various domains for decision-making purposes. On account of this, we develop a visual sentiment analysis system, which can classify image expression. The system classifies images by taking into account six different expressions such as anger, joy, love, surprise, fear, and sadness. In our study, we propose an expert system by integrating a Deep Learning method with a Belief Rule Base (known as the BRB-DL approach) to assess an image’s overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 34 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Moreover, this will make the diagnosis of PD more accurate and effective. A more efficient system can be built for PD detection using Belief Rule Based Expert Systems (BRBES) [10][11][12][13]25,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this will make the diagnosis of PD more accurate and effective. A more efficient system can be built for PD detection using Belief Rule Based Expert Systems (BRBES) [10][11][12][13]25,34,37].…”
Section: Discussionmentioning
confidence: 99%
“…The main aim of this research was to conduct a comparative analysis of various speech signal features for diagnosing Parkinson's disease using disjunctive BRBES [15,19,29] with optimization. It was observed that exploitive BRBaDE outperforms explorative BRBaDE, Genetic Algorithm and FMINCON in this task.…”
Section: Discussionmentioning
confidence: 99%
“…The second method is to test the correlation of the data using the product moment and to determine the validity of the data using R table, while to test the consistency of the measuring instrument using cronbach alpha. The third method is the scientific method for solving problems by using the rule-based reasoning method [20], [21].…”
Section: Methodsmentioning
confidence: 99%